Cystic Fibrosis Mini Review - Baran Ezequiel (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Cystic Fibrosis (CF) is a complex, multisystemic disease that predominantly affects the gastrointestinal and pulmonary tracts. The essential alteration is the production of abnormal secretions in the exocrine glands, including the salivary and sweat glands, the pancreas, the large intestine, and the tracheobronchial tree [1].